A Young Female with Trichobezoar: A Case Report - Poudel, Rajesh; Parajuli, Anwiti; Bhattarai, Humnath; Bashyal, Ravi; Dhakal, Sushil (Journal of Universal College of Medical Sciences, 2023)
Trichobezoars are rare mass of hair usually located in the stomach, but may extend into the small intestine and sometimes up to large bowel. It is usually associated with a history of psychiatric disorders such as trichophagia and trichotillomania. We present a case of trichobezoar in a 14-year-old female with decreasing density of hair, abdominal pain, vomiting and history of trichophagia. The diagnosis was conﬁrmed by CT scan. The patient was managed by exploratory laparotomy with gastrotomy.